Evidence for active control of tongue lateralization in Australian English /l. (May 2021) - Ying, Jia; Shaw, Jason A.; Carignan, Christopher; Proctor, Michael; Derrick, Donald; Best, Catherine T.
Highlights: Para- and mid-sagittal gestures in /l/ examined with electromagnetic articulography (3D EMA). Lateral channel formation involves parasagittal asymmetries in tongue blade movements. Tongue lateralization is under task-directed control during /l/ production. Abstract: Research on the temporal dynamics of /l/ production has focused primarily on mid-sagittal tongue movements. This study reports how known variations in the timing of mid-sagittal gestures are related to para-sagittal dynamics in /l/ formation in Australian English (AusE), using three-dimensional electromagnetic articulography (3D EMA). The articulatory analyses show (1) consistent with past work, the temporal lag between tongue tip and tongue body gestures identified in the mid-sagittal plane changes across different syllable positions and vowel contexts; (2) the lateral channel is largely formed by tilting the tongue to the left/right side of the oral cavity as opposed to curving the tongue within the coronal plane; and, (3) the timing of lateral channel formation relative to the tongue body gesture is consistent across syllable positions and vowel contexts, even as the temporal lag between tongue tip and tongue body gestures varies. This last result is particularly informative with respect to theoretical hypotheses regarding gestural control for /l/s, as it suggests that lateral channel formation is actively controlled as opposed to resulting as a passive consequence of tongue stretching. These results are interpreted as evidence that the formation of the lateral channel is a primary articulatory goal of /l/ production in AusE.